A Review of Vancomycin-Resistant Staphylococcus aureus Prevalence in Egypt and Saudi Arabia - Taha, Ahmed Elsayed (Asian Journal of Biological and Life Sciences, 2019)
Staphylococcus aureusis considered an important and dangerous pathogen worldwide.Vancomycin was extensively used for treatment of the emerging methicillin-resistantStaphylococcusaureus(MRSA), but this led to the emergence of vancomycin-resistantStaphylococcus aureus(VRSA). Epidemiological and molecular data on VRSA are still scarce in both Egypt and SaudiArabia. We conducted the present study to review the emergence of VRSA in Egypt and SaudiArabia until December 2018. Among 220 VRSA isolates reported, only 10 of them were detectedin Saudi Arabia and the remaining 210 were detected in Egypt. Nearly, all the reported VRSAisolates were multidrug resistant. Many factors contribute to differences in the prevalence ofVRSA between Egypt and Saudi Arabia. Accurate diagnostic techniques, stringent infection control,rationale antibiotic use, environmental hygiene and improving the knowledge of the healthcareworkers about VRSA in Saudi Arabia are proved to be effective in limiting its spread.
Keywords: MDR; MIC; MRSA; Staphylococcus Aureus; Vancomycin; VRSA